HGG-40. FOCUSED ULTRASOUND ENHANCES ETOPOSIDE DELIVERY IN A MURINE PONTINE GLIOMA MODEL. (1st June 2021) - Englander, Zachary; Wei, Hong-Jian; Pouliopoulos, Antonios; Yoh, Nina; McQuillan, Nicholas; Tazhibi, Masih; Wang, Tony; Bruce, Jeffrey; Canoll, Peter; Feldstein, Neil; Zacharoulis, Stergios; Konofagou, Elisa; et al.
Abstract: Background: Diffuse intrinsic pontine glioma (DIPG) is a devastating pediatric brain cancer with limited treatment options and poor survival. The delivery of systemic therapies in this disease is severely limited by the blood-brain barrier (BBB). Focused ultrasound combined with intravenous microbubbles (FUS+MB) can effectively open the BBB permitting the entry of drugs across the cerebrovasculature. Etoposide is a chemotherapy frequently used in pediatric oncology with well-established anti-tumor effects but limited efficacy when administered systemically in DIPG. Given that FUS+MB in DIPG is not well studied, our goal was to determine the feasibility of ultrasound-mediated BBB opening and etoposide delivery in a preclinical murine pontine glioma model. Methods: A syngeneic, orthotopic model was established by stereotactic injection of PDGF-B+PTEN-/-p53-/- murine glioma cells into the pons of B6 albino mice. Mice were randomly divided into control (n=6) or FUS+MB groups (n=6). A single-element, spherical-segment FUS transducer (center frequency=1.5MHz) driven by a function generator through a power amplifier was used with concurrent microbubble injection to sonicate the tumor and its margins on post-injection day 14. Immediately after treatment, 5 mg/kg of intraperitoneal etoposide was administered to all 12 mice. All animals underwent cardiac puncture and blood sampling, followed by transcardiac perfusion and brain harvesting. Liquid chromatography-mass spectometry was performed on both serum and tumor tissue to measure etoposide levels. Results: Contrast-enhanced MRI demonstrated successful BBB opening in all FUS+MB mice. Compared to control (mean=20.98ng/g), etoposide concentration in the sonicated tumor tissue (mean=164.77ng/g) was nearly eight times greater. Lastly, the mean brain tumor–to-serum ratio was more than fivefold higher in the treated mice (1.50%) compared with the control mice (0.28%) (P<0.005). Conclusions: FUS+MB is hereby shown successful in BBB opening and enhanced delivery of etoposide in a preclinical pontine glioma model.